ENVIRONMENTAL DETERMINANTS OF FIRM VALUE: THE MODERATING EFFECT OF INDEPENDENT COMMISSIONERS IN INDONESIA’S MINING SECTOR - Vini Melyati Putri; Henny Wirianata (Graduate Program of Universitas Tarumanagara, 2026)
Firm value serves as a main indicator reflecting investors’ perceptions of a corporate’s performance, either in financial and non-financial aspects. This study seeks to empirically examine regarding the influence of environmental performance, environmental cost, also environmental disclosure to firm value, with the proportion of independent commissioners acting as a moderating variable in these relationships. The research objects consist of companies within the mining industry sector, including coal, metal, and oil and gas firms written on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. Purposive sampling was employed in this study, resulting in a final sample of 17 companies that met the selection criteria. The study underwent several classical assumption tests, such as normality, multicollinearity, autocorrelation, and heteroskedasticity tests. Data processing were carried out utilizing a panel data regression through the EViews 12 software. The findings demonstrate that environmental performance and environmental cost have no significant effect on firm value. On the other side, environmental disclosure and the proportion of independent commissioners exert a negative influence on firm value. Furthermore, the results indicate that independent commissioners fails to moderate the relationship between the three environmental variables and firm value. Nonetheless, both the independent and moderating variables collectively have a significant simultaneous affect the firm value.